2006
DOI: 10.1300/j396v27n03_03
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Message Sidedness and Credibility on Healthy Eating to Prevent Cancer

Abstract: This study uses an experimental approach to test the influence of message sidedness and credibility on the attitude and intention toward following the guidelines for healthy eating and preventing cancer. The findings indicate a strong effect of credibility on attitude as well as intention. The influence of message sidedness is significant with respect to attitude, but not significant on intention. Implications for marketers in terms of message strategy are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 26 publications
1
6
1
Order By: Relevance
“…High levels of source credibility can increase the audience's confidence in their attitudes and facilitate later retrieval of information contained in the message (Brinol et al, 2004). These results are consistent with the finding that health experts are more effective than celebrities in encouraging preventive health care (Arora and Arora, 2006).…”
Section: Ageing and Mental Healthsupporting
confidence: 77%
“…High levels of source credibility can increase the audience's confidence in their attitudes and facilitate later retrieval of information contained in the message (Brinol et al, 2004). These results are consistent with the finding that health experts are more effective than celebrities in encouraging preventive health care (Arora and Arora, 2006).…”
Section: Ageing and Mental Healthsupporting
confidence: 77%
“…This could be problematic because hedging might enhance scientists’ trustworthiness while decreasing the believability of the research being reported. Past research has found that scientists’ trustworthiness and public perception of research recommendations are positively correlated (Arora & Arora, 2006); however, future work should continue to explore if and how these variables are related.…”
Section: Discussionmentioning
confidence: 99%
“…The purpose of the present study was to test whether hedging does affect news consumers (positively or negatively). On a practical level, scientists are justifiably concerned about how media portrayals of science affect their credibility and, by extension, public support for scientific research and funding (Hartz & Chappell, 1997) and public adherence to research recommendations (Arora & Arora, 2006). Some within the scientific community are so concerned that they have become wary of interacting with the press (Hartz & Chappell, 1997).…”
mentioning
confidence: 99%
“…Extant research has focused on the effects of either two-sided messages related to non-news materials or news pertaining to policies and non-health issues. For example, Arora and Arora (2006) examined the effects of two-sided health booklets and demonstrated that these non-news sources enhanced attitudes toward the advocated health behaviors. Jensen and Hurley (2012) explored responses to news articles with conflicting views about dioxin regulation and wolf reintroduction policies; when reading two articles with conflicting views as opposed to a single one-sided article, people expressed greater uncertainty.…”
Section: Audience Responses To Two-sided Media Coveragementioning
confidence: 99%